2016
DOI: 10.17219/acem/62430
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of Blood Vessel After the Administration of the Plasmid Encoding Ang-1 Gene in Fischer Rats

Abstract: Approximately 1% of patients with peripheral artery disease develop critical lower limb ischemia (CLI) with an unfavorable prognosis. Within one year after the diagnosis, more than 30% of patients with lower limb CLI require amputation [1][2][3][4].The development of endovascular treatment using angioplasty and stents have decreased the amputation rate among patients with CLI. HowCardiovascular disease is the leading cause of death in the Western world and the World Health Organization estimates that over 17 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Quartu et al [4] reported that the administration of frankincense essential oils (unsaturated fatty acids containing DHA and eicosapentaenoic acid) before cerebral ischemia can reduce the inflammatory response of brain tissue by downregulating the expression of COX-2 and provide nutritional support to damaged brain tissue, improving the cell survival rate and thus reducing cerebral ischemia/reperfusion injury. Paterniti et al [31] confirmed that DHA can significantly reduce inflammation and tissue damage after traumatic spinal cord injury. Further studies have shown that DHA can alleviate cerebral ischemia/reperfusion injury, maintain blood-brain barrier integrity, and reduce blood-brain barrier permeability [5].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Quartu et al [4] reported that the administration of frankincense essential oils (unsaturated fatty acids containing DHA and eicosapentaenoic acid) before cerebral ischemia can reduce the inflammatory response of brain tissue by downregulating the expression of COX-2 and provide nutritional support to damaged brain tissue, improving the cell survival rate and thus reducing cerebral ischemia/reperfusion injury. Paterniti et al [31] confirmed that DHA can significantly reduce inflammation and tissue damage after traumatic spinal cord injury. Further studies have shown that DHA can alleviate cerebral ischemia/reperfusion injury, maintain blood-brain barrier integrity, and reduce blood-brain barrier permeability [5].…”
Section: Discussionmentioning
confidence: 97%
“…Angiopoietins are proteins secreted by vascular endothelial cells, pericytes, myocytes, and mesenchymal cells. The competitive binding of Ang-1 and Ang-2 to Tie-2 plays an important role in blood-brain barrier permeability, endothelial cell fusion, and the response of blood vessels to different organ systems and disease states [31][32][33]. Further studies showed that downregulated Ang-1 expression is closely related to blood-brain barrier function after cerebral ischemia and that the administration of Ang-1 can alleviate injury to the blood-brain barrier induced by ischemia, while Ang-2 and VEGF cause damage blood-brain barrier permeability [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The ANG-1 plasmid was prepared analogously. The whole process has already been described in detail [16].…”
Section: Preparation Of Plasmid Dnamentioning
confidence: 99%